HUBUNGAN KETERTARIKAN INTERPERSONAL DENGAN WORK ENGAGEMENT PEGAWAI PT. SALINDO BERLIAN MOTOR JAKARTA - Yuningsih, Ayu; Mariyanti, Sulis (Jurnal Psikologi, 2015)
AbstractEmployees who have a work engagement is employees who are willing to fight and diligently do the work, and feel one with the company. One of the factors that affect the employees tied to his work is the existence of interpersonal attraction, namely the existence of a positive assessment against a co-worker, that raises the closeness and togetherness. The purpose of this research was to know relationship interpersonal attraction and work engagement. The design of this study is a quantitative non experimental with saturated sampling technique , totaling 60 employees of PT . Salindo Berlian Motors . The coefficient of reliability of the measuring instrument interpersonal attraction ( α ) = 0.924 with 36 items is valid , and measuring work engagemet ( α ) = 0,959 with 58 items is valid . The result of Pearson product moment correlation between interpersonal attraction and work engagement is obtained sig ( p ) = . 000 ( p<0.05) with the value of the correlation ( r ) = . 779. Categorization test results obtained by the level of interpersonal attraction and work engagement of employees tends to be low , and the dominant dimensions of work engagement is owned vigor . Keywords:  interpersonal attraction, work engagement, employee AbstrakPegawai yang memiliki work engagement adalah pegawai yang mau berjuang dan tekun melakukan pekerjaan, serta merasa menyatu dengan perusahaan. Salah satu faktor yang memengaruhi pegawai terikat dengan pekerjaannya adalah adanya ketertarikan interpersonal, yaitu adanya penilaian positif terhadap rekan kerja, yang menimbulkan kedekatan dan kebersamaan. Tujuan dari penelitian ini untuk mengetahui hubungan ketertarikan interpersonal dan work engagement. Rancangan penelitian ini adalah kuantitatif non eksperimen dengan  teknik sampling jenuh, berjumlah 60 pegawai PT. Salindo Berlian Motor. Koefisien reliabilitas dari alat ukur interpersonal attraction (α)= 0,924 dengan 36 item valid, dan alat ukur work engagemet (α)= 0,959 dengan 58 item valid. Hasil uji korelasi pearson product moment antara ketertarikan interpersonal dan work engagement diperoleh nilai sig (p)=.000 (p<0.05) dengan nilai korelasi (r)=.779. Hasil uji kategorisasi diperoleh tingkat ketertarikan interpersonal dan work engagement pegawai cenderung rendah, dan dimensi dominan dari work engagement yang dimiliki adalah vigor.Kata kunci:  interpersonal attraction, work engagement, pegawai